Late Cenozoic contractional evolution of the current arc-volcanic region along the southern Central Andes (35°20′S). (August 2015) - Tapia, Felipe; Farías, Marcelo; Naipauer, Maximiliano; Puratich, Jacqueline
Highlights: Synorogenic deposits evidence that the arc region has underwent shortening since the late Miocene. Out-of-sequence thrusting event was identified through the southern Central Andes. Contractional tectonics would dominate the evolution of the arc region since the Pliocene. The southward increase of the erosion rate would have triggered the out-sequence thrusting in the internal region of the Andes Cordillera. Abstract: The Andean internal zone records deformation, uplift and erosion that serve as proxies of variations on mountain building dynamics. Hence, the study of this region would give keys to understand the factors controlling the orogenic evolution. Structural, stratigraphic and geochronological data in the Andean internal zone at 35°20′S evidence that this region has only underwent contractional deformation since the late Miocene up to present, differing from coeval Pleistocene extensional tectonics affecting the retro-arc. Contractional deformation was characterized by the development of a piggy-back basin in the latest Miocene filled by synorogenic deposits. Afterward, an out-of-sequence thrusting event affected the region since at least the Pliocene until the Present. Shortening in the inner part of the Andean orogen would be favored by both the high orthogonality of the out-sequence structures with respect to the plate convergence vector and by the minor resistance to shortening produced by the southward decrease of the orogen height and by the removal of material via erosion of the uplifted mountain belt. In contrast, oblique structures, as those described farther north, accommodate strike-slip displacement. Likewise, we propose that erosion from the inner orogen favored the prolongation of the out-of-sequence thrusting event until the Present, differing from the situation north of the 34°S where this event ended by the Pliocene.